Mechanistic investigation of RhB photodegradation under low power visible LEDs using a Pd-modified TiO2/Bi2O3 photocatalyst: Experimental and DFT studies. (March 2022) - Sharma, Shankar; Mittal, Anuj; Chauhan, Nar Singh; Saini, Sangeeta; Yadav, Jyoti; Kushwaha, Manoj; Chakraborty, Rahul; Sengupta, Shantanu; Kumari, Kavitha; Kumar, Naveen
Abstract: An energy efficient hydrothermal route has been adopted for the synthesis of binary TiO2 /Bi2 O3, followed by a chemical method to prepare a series of novel ternary TiO2 /Bi2 O3 /Pd nanocomposites. The characteristics of the resulting composites were uncovered using advanced techniques. The results revealed the formation of the desired products with improved characteristics. Among the binary and ternary samples, TiO2 /Bi2 O3 (15%) and TiO2 /Bi2 O3 (15%)/Pd (3%) showed the best activity toward the degradation of RhB under irradiation with visible LEDs. After cyclic experiments, no significant decrease in the efficiency was detected. The degradation pathway of RhB was uncovered using density functional theory (DFT) and mass spectroscopy. From scavenger studies, superoxide anion radical and holes were found the prominent active species responsible for the removal of RhB. The as-synthesized composites are useful for the fabrication of low power consuming photoreactors for use in efficient water purification systems. Highlights: Low power consumption visible LEDs were used for the removal of RhB. The complete removal of RhB was attained in 40 min. The removal of RhB follows a de-ethylation pathway as confirmed by LCMS. The photocatalyst was stable up to 5 cycles without any significant loss in activity. Holes were the prominent species for the removal of RhB.